Community forestry in the United States : learning from the past, crafting the future - Baker, Mark, 1961-; Kusel, Jonathan (Island Press, 2003)
"Community forestry offers an alternative to current forestry practices, representing a new approach that focuses on sustaining both the health of forest ecosystems and the health and well-being of local communities and workers. This book not only clarifies the state of the movement, but also suggests a trajectory and process for its continued development. Community Forestry in the United States is an essential reference for community forestry supporters and practitioners, students and scholars of social movements, and all those concerned with the health and well-being of ecosystems and communities."--Jacket